Health, communication and multicultural communities : topics on intercultural communication for healthcare professionals - Valero Garcés, Carmen (Cambridge Scholars Publishing, 2014)
"Communicating in multicultural settings is a field of central interest to those involved in ensuring access to healthcare. Ever-increasing migration requires access to essential legal, medical and social services. This book provides an overview of current issues in this field through a multi-faceted approach, situating the work of potential healthcare professionals and intercultural intermediaries in the broader context of public service providers and practitioners. The book is not oriented towards one population in particular; rather it is directed towards multiple groups, mainly to students of the health sciences and medical professionals interested in communicating with migrants and visitors, and those who have to work in multicultural settings. It is not a theoretical book, nor is it rule-based by any means. It is a handbook oriented towards reflection and practice resulting from years of experience training mediators, interpreters and translators working in minority languages within multicultural settings. It can be used for self-study and independent learning, but will also be extremely useful to teachers and trainers of future doctors and medical staff who seek materials or readings for their classes. Furthermore, it represents an excellent resource for mediators, interpreters and translators who want to learn more about communication in healthcare setting"--Provided by publisher